The Hurricane Sandy Rebuilding Task Force's Infrastructure Resilience Guidelines An Initial Assessment of Implementation by Federal Agencies - Finucane, Melissa L (RAND Corporation, 2014)
To ensure that federal agencies incorporate key principles of resilience into their formulation, evaluation, and prioritization of infrastructure investments related to Sandy rebuilding, the Presidential Hurricane Sandy Rebuilding Task Force developed its Infrastructure Resilience Guidelines. RAND researchers conducted an initial assessment of federal agencies' implementation of the guidelines to identify the main opportunities and challenges.